Alone together : love, grief, and comfort during the time of COVID-19 - Haupt, Jennifer (Journalist) (Central Avenue Publishing, 2020)
Alone Together: Love, Grief, and Comfort During the Time of COVID-19 is a collection of essays, poems, and interviews to serve as a lifeline for negotiating how to connect and thrive during this stressful time of isolation as well as a historical perspective that will remain relevant for years to come. All net profits will be donated to The Book Industry Charitable Foundation, a nonprofit organization that coordinates charitable programs to strengthen the bookselling community. Ms. Haupt rallied a diverse roster of more than 90 authors to contribute their work to Alone Together, free of charge, including Kwame Alexander, Jenna Blum, Andre Dubus III, Jamie Ford, Nikki Giovanni, Pam Houston, Jean Kwok, Major Jackson, Caroline Leavitt, Ada Limón, Dani Shapiro, David Sheff, Garth Stein, Luis Alberto Urrea, Steve Yarbrough, and Lidia Yuknavitch. The overarching theme is how this age of isolation and uncertainty holds the possibility of changing us as individuals and a society.